Biliary effects of liraglutide and sitagliptin, a 12‐week randomized placebo‐controlled trial in type 2 diabetes patients. Issue 12 (30th August 2016) - Smits, Mark M.; Tonneijck, Lennart; Muskiet, Marcel H.A.; Hoekstra, Trynke; Kramer, Mark H.H.; Diamant, Michaela; Nieuwdorp, Max; Groen, Albert K.; Cahen, Djuna L.; van Raalte, Daniël H.
Abstract : Aims: Treatment with glucagon‐like peptide (GLP)‐1 receptor agonists or dipeptidyl peptidase (DPP)‐4 inhibitors might increase gallstone formation; however, the mechanisms involved are unknown. We aimed to assess the effects of these drugs on gallbladder volume and bile acid profile. Materials and methods: A total of 57 type 2 diabetes patients (mean ± SD age, 62.8 ± 6.9 years; BMI, 31.8 ± 4.1 kg/m 2 ; HbA1c, 7.3% ± 0.6%), treated with metformin and/or sulfonylureas, were included in this 12‐week randomized, placebo‐controlled, double‐blind, single‐centre trial between July 2013 and August 2015 at the VU University Medical Center, the Netherlands. Patients received the GLP‐1 receptor agonist liraglutide, the DPP‐4 inhibitor sitagliptin or matching placebo for 12 weeks. Gallbladder fasting volume and ejection fraction were measured using ultrasonography after a high‐fat meal. Serum bile acids were measured in the fasting and postprandial state and in faecal samples. The trial was registered atClinicalTrials.gov (NCT01744236). Results: Neither liraglutide nor sitagliptin had an effect on gallbladder fasting volume and ejection fraction (p > .05). Liraglutide increased serum levels of deoxycholic acid in the fasting state [0.20 µmol/L (95% CI 0.027‐0.376), p  =  0.024] and postprandial state [AUC 40.71 (13.22‐68.21), p = 0.005] and in faeces [ratio 1.5 (1.03‐2.19); p = 0.035]. Sitagliptin had no effect on serum bile acids, but increased faecal levels of chenodeoxycholic acid [ratio 3.42 (1.33‐8.79), p = 0.012], cholic acid [ratio 3.32 (1.26‐8.87), p = 0.017] and ursodeoxycholic acid [ratio 3.81 (1.44‐10.14), p = 0.008]. Conclusions: Neither liraglutide nor sitagliptin has an effect on gallbladder volume. Observed changes in bile acids with liraglutide suggest alterations in the intestinal microbiome, while sitagliptin appears to increase hepatic bile acid production.